Analisis Pengaruh Likuiditas, Profitabilitas, Insider Ownership, Institutional Ownership dan Pertumbuhan Perusahaan terhadap Kebijakan Dividen pada Perusahaan Sektor Properti, Real Estate dan Konstruksi Bangunan - Irene Mardian Puteri; Sudarto Sudarto; Sulistyandari Sulistyandari (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The study titled liquidity, profitability, insider ownership, institutional ownership and growth of the company on dividend policy company property sector, real estate and building construction to determine the influence of the five variables on dividend policy on the company's property sector, real estate and construction of buildings. This research was conducted during the period 2010-2014. The populations in this study are all companies listed in Indonesia Stock Exchange during the study period of data collection method using purposive sampling, in order to obtain 6 companies. This study used panel data regression analysis with a model Fixed Effect and the tool to analyze the data used Eviews 8. Testing the hypothesis using by the coefficient of determination, t-test statistics and F-test statistics.The results showed that liquidity does not affect the dividend policy, profitability does effect on dividend policy, insider ownership does not affect the dividend policy, institutional ownership does affect the dividend policy, the company's growth does not effect on dividend policy. The implication of this research for the company to consider profits as a main consideration to dividend policy as well as the company continues to invest despite profit increase or decrease.